The chromatin remodeling complex NoRC controls replication timing of rRNA genes - Li, Junwei (Nature Publishing Group, 2005)
The ATP-dependent chromatin remodeling complex NoRC silences a fraction of mammalian ribosomal RNA genes (rDNA) by establishing heterochromatic structures at the rDNA promoter. Here we show that NoRC also plays a role in replication timing of rDNA. rDNA is replicated in a biphasic manner, active genes (∼60%) replicating early and silent ones (∼40%) replicating late in S-phase. The chromatin structure that marks active and silent rDNA repeats is propagated during cell division. To examine the function of NoRC in epigenetic inheritance and replication timing, we have monitored the chromatin structure, transcriptional activity and replication timing of rDNA in a cell line that moderately overexpresses NoRC. NoRC is exclusively associated with late-replicating rDNA arrays. Overexpression of NoRC silences rDNA transcription, reduces the size and number of nucleoli, impairs cell proliferation and resets replication timing from early to late. The results demonstrate that NoRC is an important determinant of replication timing and epigenetic marks are heritably maintained through DNA replication.